Pestisida Organoklorin dalam Air dari Daerah Jabodetabek: Studi Pada Daerah Padat Penduduk - Shoiful, Ahmad; Nugroho, Rudi; Fujita, Hiroyuki; Honda, Katsuhisa (Center for Environmental Technology, 2015)
Organochlorine pesticides (OCPs) in waters from five sampling point in Jabodetabek area have been determined using HRGC-HRMS. A total of 21 OCPs have been analyzed, however only few of OCPs were detected. Among HCH isomers, only Ã¯ÂÂ¡-HCH and lindane (Ã¯ÂÂ§-HCH) were detected with concentration in the range of ND-0,25 ng/L and 0,083 Ã¢â‚¬â€œ 0,82 ng/L, respectively. Interesting result was found, where HCB was detected in relatively high in water of Ciliwung river, Pluit Jakarta with concentration of 688,28 ng/L. HCB is a compound which is not only intentionally produced as pesticide, but also unintentionally produced from industrial by-product. Therefore, contamination of the river water may come from industrial processes which are located near sampling point. If compared with river water quality criteria of PP No.82 Tahun 2001, it results were below the standard of river water quality Class I.Ã‚Â Keywords : organochlorine pesticides (OCPs), waters, Indonesia, industrial by-products.